2016
DOI: 10.15256/joc.2016.6.72
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity: What Do We Know? What Should We Do?

Abstract: Multimorbidity, which is defined as the co-occurrence of two or more chronic conditions, has moved onto the priority agenda for many health policymakers and healthcare providers. Patients with multimorbidity are high utilizers of healthcare resources and are some of the most costly and difficult-to-treat patients in Europe. Preventing and improving the way multimorbidity is managed is now a key priority for many countries, and work is at last underway to develop more sustainable models of care. Unfortunately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
229
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(239 citation statements)
references
References 24 publications
4
229
1
5
Order By: Relevance
“…Using Q-methodology, we identified three viewpoints held by patients with multi-morbidity on the important aspects of PCC delivery in the primary care setting, representing [1] the prepared proactive patient, [2] the everyday patient, and [3] the vulnerable patient. The results of this study are important for improving care delivery for patients with multi-morbidity in primary care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Q-methodology, we identified three viewpoints held by patients with multi-morbidity on the important aspects of PCC delivery in the primary care setting, representing [1] the prepared proactive patient, [2] the everyday patient, and [3] the vulnerable patient. The results of this study are important for improving care delivery for patients with multi-morbidity in primary care.…”
Section: Resultsmentioning
confidence: 99%
“…We define multi-morbidity as the co-existence of two or more chronic conditions in one patient. Patients with multi-morbidity are often considered to constitute a vulnerable and complex population with a high risk of mortality and high utilization of care, and they often are less satisfied with their care [3,4]. Moreover, a systematic review showed that quality of life decreases with an increasing number of diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity, the presence of multiple chronic conditions or diseases in the same individual [4,5,6], is becoming progressively more common [7]. Currently, an estimated 50 million people in the European Union suffer from multimorbidity [8], making it the most common chronic condition [5]. Also, in America, the number of people with chronic conditions is projected to increase steadily for the next 30 years [9].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness has been associated with frailty (Herrera‐Badilla, Navarrete‐Reyes, Amieva, & Avila‐Funes, ) and a fall in the previous year (Hajek & Konig, ). Hence, the co‐occurrence of these and other health problems is common (Navickas, Petric, Feigl, & Seychell, ; Onder et al, ).…”
Section: Introductonmentioning
confidence: 99%